A brief review of anaerobic membrane bioreactors emphasizing recent advancements, fouling issues and future perspectives. (15th September 2020) - Shahid, Muhammad Kashif; Kashif, Ayesha; Rout, Prangya Ranjan; Aslam, Muhammad; Fuwad, Ahmed; Choi, Younggyun; Banu J, Rajesh; Park, Jeong Hoon; Kumar, Gopalakrishnan
Abstract: This review summarizes the recent development and studies of anaerobic membrane bioreactor (AnMBR) to control fouling issues. AnMBR is an emerging waste water treatment technology mainly because of its low sludge residual, high volumetric organic removal rate, complete liquid-solid separation, better effluent quality, efficient resource recovery and the small footprint. This paper surveys the fundamental aspects of AnMBRs, including its applications, membrane configurations, and recent progress for enhanced reactor performance. Furthermore, the membrane fouling, a major restriction in the practical application of AnMBR, its mechanism and antifouling strategies like membrane cleaning, quorum quenching, ultrasonic treatment, membrane modifications, and antifouling agents are briefly discussed. Based on the review, the key issues that require urgent attention to facilitate large scale and integrated application of AnMBR technology are identified and future research perspectives relating to the prevalent issues are proposed. Highlights: Recent advancements in anaerobic membrane bioreactors (AnMBR) are concisely reviewed. The fouling mechanism and the advanced antifouling strategies are summarized. Costs incurred in different operational steps of AnMBR are compared. Future research is needed for techno-economic analysis of large scale applications.